The dna barcoding data and genetic distance of leaf beetles (Coleoptera, Chrysomelidae) in Vietnam - Dinh, Nguyen Thi (Academia Journal of Biology, 2020)
DNA barcoding is a useful tool in identifying species, biodiversity assessment, and revealing phylogenetic relationships of living organisms in the world. However, the DNA barcode data for leaf beetles in Vietnam is lacking. In this study, sixteen DNA sequences of 658 bp of COI gene from nine species (five genera; three subfamilies) of Chrysomelidae in Vietnam were (obtained). Intra- and inter-specific diversities, and phylogenetic relationships of these species were analyzed.